Korelasi Antara Intensitas Penggunaan Media Sosial dan Penurunan Kualitas Interaksi Sosial Siswa - Taj Jauhara Saripudin, Cantika Nisrina; Nazwa, Fatimah An; Khotimah, Raihani Nurul; Wati, Talitha Arista; Yosep, Zahra Audyna; Prihantini, Prihantini (Lembaga Intelektual Muda (LIM) Maluku, 2025)
This study examines the impact of social media use on the quality of student social interaction in the digital era. Technological developments, particularly smartphones and the internet, have changed the way humans interact, with social media being the primary platform for communication. This study uses a literature study method, examining various research and theories related to social media, social interaction, and its impact on students. The main source of data for this research is scientific articles published and identified by Google Scholar. The results of the analysis show that the intense use of social media can reduce the frequency of direct interaction, affect non-verbal communication skills, and reduce participation in social activities in schools. However, social media can also be used positively for learning if used wisely and supported by good digital literacy. Other factors such as parenting patterns and social environment also play an important role in moderating the impact of social media. This study concludes the importance of balancing digital activities and direct social interaction to maintain the quality of students' social interaction